Fyre - Sage, Angie (Sage, Angie. Septimus Heap, 2013)
Septimus must battle the remnants of the Dark Domaine, which will remain until the power of the evil Two-Faced Ring is destroyed forever. To accomplish that, the ancient Alchemie Fyre must be relit -- a task that sends Septimus to the very origins of Magyk and Physik, testing both his skills, and his loyalties to ExtraOrdinary Wizard, Marcia Overstrand, and Alchemist Marcellus Pye.